Drug encapsulation and release behavior of telechelic nanoparticles. (25th September 2015) - Zhang, Shimiao; Arshad, Muhammad; Ullah, Aman
Abstract: The encapsulation and release of hydrophobic drug, carbamazepine (CBZ) was investigated using three previously synthesized amphiphilic Lipid-b-poly(ethylene glycol) (Lipid-PEG) conjugates. Their micellization, drug encapsulation, and release behavior was investigated by dynamic light scattering (DLS), transmission electron microscope (TEM), and fluorescence spectroscopy. The highest capacity of drug entrapment was observed for the CPE-PEG-a telechelic with the shorter PEG block and the size of the nanoparticles decreased evidently after the drug was loaded, while a slight decrease in size was also observed for the CPE-PEG-b telechelic with longer PEG block and the three-armed CPE-GE conjugate. TEM images showed that all three types of the drug-loaded micelles had spherical or near-spherical morphology. In the study of the in vitro drug release, slower drug-release patterns were observed for CPE-PEG-a and CPE-GE micelles. Almost all the drug entrapped inside the three types of micelles could be released within 50 h.